Factor Endowment, Structural Coherence, and Economic Growth - Che, Natasha (IMF Working Papers; Working Paper ;, 2012)
This paper studies the linkage between structural coherence and economic growth. Structural coherence is defined as the degree that a country's industrial structure optimally reflects its factor endowment fundamentals. The paper found that at least for the overall capital, the shares of capital intensive industries were significantly bigger with higher initial capital endowment and faster capital accumulation. Moreover, there is a positive relationship between a country's aggregate output growth and the degree of structural coherence. Quantitatively, the structural coherence with respect to the overall capital explains about 30% of the growth differential among sample countries.